Time and Speed of Stirring Treatment in Adsorption Effectiveness of Coffee Processing Waste Water - Elida Novita; Hendra Andiananta Pradana; Siti Nur Aenia (Jurnal Keteknikan Pertanian, 2021)
Processing of coffee with wet processing method produces a lot of waste water from the results of the vines, pulping, and the washing result of fermentation. The wastewater has the potential to pollute the environment in case of no treatment. Adsorption is one method that can reduce the risk of pollution from coffee processing wastewater. The time variation and stirring speed of adsorption may affect the improvement of the quality of wastewater. The study aims to identify the influence of time and speed stirring towards the efficiency of decreasing the parameter turbidity and color in the adsorption of coffee wastewater using activated carbon from the coffee pulp. Carbon from coffee pulp was activated by using NaOH 1 M. The parameters observed in the adsorption i.e turbidity and color. The time used in stirring i.e 60 minutes 65 minutes, and 70 minutes with each speed of 60 rpm, 90 rpm, and 120 rpm. The research result shows that the best stirring time and speed treatment was 60 Minutes/120 rpm. The time and stirring treatment of 60 minutes/120 rpm in coffeeprocessing wastewater adsorption is the best effective treatment in decreasing turbidity and color parameters respectively, 93.13% and 83.93%.